Long-term Outcome of Subacute Thyroiditis - Görges, Julia; Ulrich, Jan; Keck, Christoph; Müller-Wieland, Dirk; Diederich, Sven; Janssen, Onno E. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Subacute thyroiditis (SAT) is a rare inflammatory disease that presents diagnostic challenges. The underlying pathophysiology and prediction of outcomes are elusive. We investigated the long-term follow-up of SAT for up to 30 years and determined predictors for later hypothyroidism.Methods SAT outcome data from 127 patients (age: 47.6 ± 11.0 yrs., BMI: 24.7±4.8 kg/m²) were analyzed retrospectively. Patients with pre-existing and known causes of hypothyroidism unrelated to SAT were excluded. We also excluded patients without an accelerated erythrocyte sedimentation rate. SAT outcome parameters included anterior neck pain or tenderness of the thyroid, inflammation markers, hypoechoic areas in thyroid ultrasound, hyperthyroidism, fine-needle aspiration, and thyroid scan. Pre-treatment TSH-levels, gender, age, ultrasound findings, anti-thyroid antibodies and markers of inflammation were considered as possible predictors of SAT outcome.Results More than 26.8% of SAT patients developed permanent hypothyroidism within 3 years of treatment. The patient groups later developing hypothyroidism did not differ in age, BMI, pre-treatment TSH levels or initial dosage of prednisolone treatment. However, high cumulative doses of prednisolone were associated with a higher prevalence of hypothyroidism. Also, women were more likely to develop hypothyroidism (OR: 3.18 (95% CI: 1.14–8.65); p=0.0176).Conclusions Our study suggests that one-quarter of patients with SAT develop hypothyroidism in the long-term. Hypothyroidism was predicted by high cumulative doses of prednisolone treatment and female gender. The reported lower prevalence of hypothyroidism in other countries may represent the faster establishment of diagnosis, different treatment protocols, or lower susceptibility to loss of thyroid function. Swift establishment of the diagnosis and rapid tapering of steroids may result in a higher proportion of patients with euthyroidism.
Keywords: thyroid; thyroiditis; antibodies; autoimmunity; hormones